Current status and potential of circular agricultural economy for sustainable development in the Mekong Delta, Vietnam - Minh, Vo Quang; Vu, Pham Thanh; Thuy, Nguyen Minh; Huong, Huynh Thi Thu; Dang, Pham Cam (Plant Science Today, 2024)
The study evaluates the circular economy's present state and its potential to advance sustainable agricultural development in Vietnam's Mekong Delta. The study has reviewed data, inherited, compared and synthesized the cycle of agricultural models, thereby making suitable recommendations for land use models. The results show that the current models can apply the cycle of models, ensuring efficiency in economic, social and environmentally sustainable development, including items and by-products of the most popular agricultural farming models that people use to generate things like rice, beef, wood, lotus seeds and fruit trees. The by-products of production and harvesting, such as straw, rice straw, rice husk, bones, fish skin, fruit tree sawdust, bagasse etc., are still plentiful but have not yet been fully utilized. Using circular economy in agricultural models can help improve economic and social efficiency and support and effectively exploit resources and human resources. Thereby orienting the cyclic model development, building product linkage chains, efficiently using resources, which can increase models' efficiency and simultaneously protecting the environment sustainability.